Vloga z informacijsko-komunikacijskimi tehnologijami podprtih kognitivno vedenjskih intervenc pri obravnavi nespečnosti v obdobju pozne odraslosti - Ficjan, Monika (Psihološka obzorja (Ljubljana), 2024)
: Insomnia, a prevalent sleep disorder in late adulthood, often disrupts the quality of life among the elderly, necessitating effective treatment strategies. Cognitive-Behavioral Therapy for Insomnia (CBT-i) emerges as a first-line treatment, offering substantial benefits through its efficacy and absence of side effects. Given the pervasive incidence of insomnia in late adulthood juxtaposed with restricted access to sleep disorder specialists, alternative, widely accessible CBT-i treatment forms are fervently explored. This narrative review investigates the potential of Information and Communication Technologies (ICT) in supporting CBT-i interventions, specifically focusing on their effectiveness and factors modulating this efficacy in treating insomnia among older adults. Additionally, this review critically assesses the prospective development and utilization of ICT-supported CBT-i interventions within Slovenia’s elderly demographic. Our conclusions suggest that ICT-supported CBT-i interventions, with particular modifications, may serve as a viable, effective approach in addressing insomnia, promoting broader and more facile use among the elderly. This modality presents a potentially impactful strategy for accessible insomnia treatment, aspiring to enhance sleep quality during late adulthood.
Keywords: cognitive-behavioural therapy for insomnia; digital technologies; digitalne tehnologije; insomnia; kognitivno-vedenjska terapija za nespečnost; late adulthood; motnje spanja; pozna odraslost; sleep disorders